Analyzing the Feasibility of Introducing Business Intelligence for Enhancing International Cooperation in the Ministry of Education, Culture, Research, and Technology of Indonesia - Nuryanto, Adi; Wijaya, Chandra; Indriati Dwi Liestiawati, Fibria (JPSI (Journal of Public Sector Innovations), 2025)
International cooperation plays a crucial role in enabling public organizations to achieve their strategic objectives by utilizing business intelligence (BI) tools for informed decision-making. The quality of data and analysis significantly influences the formulation of effective cooperation strategies, particularly in identifying challenges, opportunities, and risks. Successful cooperation also depends on the availability of adequate financial, human, and technological resources, as well as strong institutional partnerships. This study examines the potential application of Business Intelligence (BI) to strengthen the international cooperation framework within Indonesia’s Ministry of Education, Culture, Research, and Technology (MoECRT). The research addresses the current gap in optimizing data-driven policy support for international engagement, particularly in managing complex, cross-sectoral collaboration. It investigates how BI can contribute to improving strategic planning, operational efficiency, and responsiveness in foreign cooperation efforts through innovative approaches to data utilization. By analyzing Indonesia’s institutional capacity and limitations in organizing international cooperation across education, culture, research, and technology, the paper offers practical insights into how BI integration can enhance performance. The study aims to contribute to the discourse on digital transformation and innovation in public sector cooperation, providing evidence-based recommendations for elevating MoECRT’s global partnerships